2011
DOI: 10.4161/auto.7.7.15371
|View full text |Cite
|
Sign up to set email alerts
|

Liver autophagy contributes to the maintenance of blood glucose and amino acid levels

Abstract: Both anabolism and catabolism of the amino acids released by starvation-induced autophagy are essential for cell survival, but their actual metabolic contributions in adult animals are poorly understood. Herein, we report that, in mice, liver autophagy makes a significant contribution to the maintenance of blood glucose by converting amino acids to glucose via gluconeogenesis. Under a synchronous fasting-initiation regimen, autophagy was induced concomitantly with a fall in plasma insulin in the presence of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
219
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(237 citation statements)
references
References 46 publications
11
219
0
1
Order By: Relevance
“…Similar results were observed in primary mouse haematopoietic stem cells following metabolic stress due to cytokine withdrawal in vitro or nutrient starvation in vivo 54 . In addition, recent studies using liver-specific Atg7-null mice demonstrated that hepatic autophagy is critical for maintaining systemic blood glucose levels during fasting by converting autophagy-derived amino acids to glucose via hepatic gluconeogenesis 55 . Overall, these studies highlight the diverse functions of autophagy-derived amino acids in sustaining energy production via the TCA cycle and producing substrates that fuel gluconeogenesis.…”
Section: β-Oxidationmentioning
confidence: 99%
“…Similar results were observed in primary mouse haematopoietic stem cells following metabolic stress due to cytokine withdrawal in vitro or nutrient starvation in vivo 54 . In addition, recent studies using liver-specific Atg7-null mice demonstrated that hepatic autophagy is critical for maintaining systemic blood glucose levels during fasting by converting autophagy-derived amino acids to glucose via hepatic gluconeogenesis 55 . Overall, these studies highlight the diverse functions of autophagy-derived amino acids in sustaining energy production via the TCA cycle and producing substrates that fuel gluconeogenesis.…”
Section: β-Oxidationmentioning
confidence: 99%
“…22 Apart from its physiological function, autophagy can also be induced on starvation as an adaptive response that recycles macromolecules to provide nutrients and energy essential for survival. [11][12][13] Interestingly, Paneth cells of starved mice showed increased induction of autophagy. We hypothesize that the deviant granules in Paneth cells of starved mice may be caused by induction of autophagy on starvation in an attempt to maintain vital cellular functions at the expense of the physiological function of autophagy (namely, the regulation of Paneth cell granule development).…”
Section: Starvation Compromises Paneth Cells 2889mentioning
confidence: 99%
“…4 Enteral starvation and total parenteral nutrition, as applied to critically ill patients, are reported to result in increased gut wall permeability, a compromised immune system, and bacterial translocation. [5][6][7][8][9][10] Because autophagy, a process induced on starvation, [11][12][13] influences the generation of Paneth cell granules, 14 we hypothesize that enteral starvation impairs Paneth cell function, contributing to starvation-associated gut compromise.…”
mentioning
confidence: 99%
“…14 We therefore examined the concentration of each of 20 amino acids in the liver of control and colchicine-treated fish. During the measured time period of starvation, the levels of some amino acids (including branched-chain amino acids) in the liver of control fish increased gradually and significantly (Fig.…”
Section: Colchicine Treatment Affects Hepatic Carbohydrates and Protementioning
confidence: 99%